Tanggung Jawab Pemerintah Daerah Kabupaten/Kota Dalam Memenuhi Hak Anak Terlantar Untuk Memperoleh Identitas Diri - Puru, Silvia Yuniwati; Pattinasarany, Yohanes; Soplanit, Miracle (Pusat Studi Hukum dan Pemerintahan Fakultas Hukum Universitas Pattimura, 2024)
A person's identity must be given from birth. Having an identity is a human right, so the State, Government and society must uphold and respect it, such as establishing rules or policies to protect the right to obtain an identity that applies to anyone. Therefore, abandoned children also have the right to have their own identity. However, in reality, it is not uncommon for abandoned children to have no identity. These problems and some of the descriptions above show that even though there are a number of laws and regulations, there are still neglected children who do not have a proper place to live or have personal identity. The explanation above underlies the problem being discussed, namely what form of responsibility the government gives in fulfilling the rights of abandoned children to obtain self-identity and what are the legal consequences if the government ignores its responsibilities in fulfilling the rights of abandoned children to obtain self-identity. This research aims to discuss, understand and analyze the form of government responsibility in fulfilling the rights of abandoned children to obtain self-identity and also to identify what legal consequences there are if the government ignores its responsibility in fulfilling the rights of abandoned children to obtain self-identity. This research uses a normative juridical method, with a statutory approach, a conceptual approach and a comparative approach between other legal systems.